Heparan Sulfate Binding Coxsackievirus B3 Strain PD: A Novel Avirulent Oncolytic Agent Against Human Colorectal Carcinoma - Hazini, Ahmet; Pryshliak, Markian; Brueckner, Vanessa; Klingel, Karin; Sauter, Martina; Pinkert, Sandra; Kurreck, Jens; Fechner, Henry (MARY ANN LIEBERT, INC, 2018)
Coxsackievirus B3 (CVB3), a single-stranded RNA virus of the picornavirus family, has been described as a novel oncolytic virus. However, the CVB3 strain used induced hepatitis and myocarditis in vivo. It was hypothesized that oncolytic activity and safety of CVB3 depends on the virus strain and its specific receptor tropism. Different laboratory strains of CVB3 (Nancy, 31-1-93, and H3), which use the coxsackievirus and adenovirus receptor (CAR), and the strain PD, which uses N- and 6-O-sulfated heparan sulfate (HS) for entry into the cells, were investigated for their potential to lyse tumor cells and for their safety profile. The investigations were carried out in colorectal carcinoma. In vitro investigations showed variable infection efficiency and lysis of colorectal carcinoma cell lines by the CVB3 strains. The most efficient strain was PD, which was the only one that could lyse all investigated colorectal carcinoma cell lines. Lytic activity of CAR-dependent CVB3 did not correlate with CAR expression on cells, whereas there was a clear correlation between lytic activity of PD and its ability to bind to HS at the cell surface of colorectal carcinoma cells. Intratumoral injection of Nancy, 31-1-93, or PD into subcutaneous colorectal DLD1 cell tumors in BALB/c nude mice resulted in strong inhibition of tumor growth. The effect was seen in the injected tumor, as well as in a non-injected, contralateral tumor. However, all animals treated with 31-1-93 and Nancy developed systemic infection and died or were moribund and sacrificed within 8 days post virus injection. In contrast, five of the six animals treated with PD showed no signs of a systemic viral infection, and PD was not detected in any organ. The data demonstrate the potential of PD as a new oncolytic virus and HS-binding of PD as a key feature of oncolytic activity and improved safety.
Keywords: coxsackievirus B3; cancer therapy; oncolytic virotherapy; colorectal cancer; enterovirus; ADENOVIRUS-RECEPTOR; INFECTIOUS CDNA; CELL-LINES; VIRUSES; TISSUE; REPLICATION; MYOCARDITIS; RNA; THERAPY; Biotechnology & Applied Microbiology; Genetics & Heredity; Research & Experimental Medicine